2017
DOI: 10.1111/cei.12977
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus capsid VP6 tubular and spherical nanostructures act as local adjuvants when co-delivered with norovirus VLPs

Abstract: SummaryA subunit protein vaccine candidate based on norovirus (NoV) virus‐like particles (VLPs) and rotavirus (RV) VP6 protein against acute childhood gastroenteritis has been proposed recently. RV VP6 forms different oligomeric nanostructures, including tubes and spheres when expressed in vitro, which are highly immunogenic in different animal models. We have shown recently that recombinant VP6 nanotubes have an adjuvant effect on immunogenicity of NoV VLPs in mice. In this study, we investigated if the adjuv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 59 publications
2
34
0
Order By: Relevance
“…GII.17 VLP binding was analyzed using three different sources of HBGAs, human saliva, pig gastric mucin (PGM) type III (Sigma Chemicals, St Louis, MO, USA) (23) and synthetic HBGAs. Binding assays were performed using procedures described in detail elsewhere (30,48). Briefly, 96-well half-area polystyrene plates (Costar, Corning, NY) were coated with either 2.5 µg/ml PGM or 1:3000 diluted type A, B, and O saliva from adult volunteers with previously determined ABO phenotype (48).…”
Section: Hbga Carbohydrate Binding Assaymentioning
confidence: 99%
“…GII.17 VLP binding was analyzed using three different sources of HBGAs, human saliva, pig gastric mucin (PGM) type III (Sigma Chemicals, St Louis, MO, USA) (23) and synthetic HBGAs. Binding assays were performed using procedures described in detail elsewhere (30,48). Briefly, 96-well half-area polystyrene plates (Costar, Corning, NY) were coated with either 2.5 µg/ml PGM or 1:3000 diluted type A, B, and O saliva from adult volunteers with previously determined ABO phenotype (48).…”
Section: Hbga Carbohydrate Binding Assaymentioning
confidence: 99%
“…However, due to the local and systemic adverse events associated with adjuvanted vaccines [22], our hypothesis is that in the pediatric NoV vaccine candidate we developed, extremely immunogenic VP6 protein may serve to substitute the external adjuvant. To this end, we have shown that RV VP6 in our combination vaccine has an adjuvant effect on NoV immune responses in vitro and in vivo [14,[23][24][25]. The adjuvant mechanism has been studied in immortalized cell lines used as antigenpresenting cells (APCs), namely, RAW macrophages and JAWSII dendritic cells (DCs), and the results suggested that VP6 acts as an immunomodulator and immunostimulator and facilitates NoV VLPs internalization by the APCs [23].…”
Section: Introductionmentioning
confidence: 91%
“…Immunization of mice with VP6‐nanotubes could also induce the highest titres of serum IgG and mucosal IgG and IgA as well as significant IFN‐γ producing T cells, which confer a higher degree of protection when compared with the immunization with DLPs or VP6 trimers . Co‐administration of VP6 nanotubes with norovirus VLPs not only induced protective immunity against RV infection but also showed an adjuvant effect of immune response for norovirus VLPs . To support this, Rodriguez et al has investigated the adjuvant effect of VP6 nanotubes and showed that nanotubes are taken up efficiently by macrophages and dendritic cells in vitro, inducing several proinflammatory cytokines and chemokines .…”
Section: Vp6 Immunogensmentioning
confidence: 99%
“…84 Co-administration of VP6 nanotubes with norovirus VLPs not only induced protective immunity against RV infection but also showed an adjuvant effect of immune response for norovirus VLPs. [86][87][88] To support this, Rodriguez et al has investigated the adjuvant effect of VP6 nanotubes and showed that nanotubes are taken up efficiently by macrophages and dendritic cells in vitro, inducing several proinflammatory cytokines and chemokines. 87,89 VP6 nanotubes were also indicated to support the internalization of co-delivered norovirus VLPs to the antigen presenting cells.…”
Section: Vp6 Dnamentioning
confidence: 99%